A methodological framework for the implementation of an interdisciplinary business analytics program using ordinal game theory - St. John, Jeremy; St. John, Karen; Ceballos, Ruben (Journal of education for business, 2023)
The authors' aim was to present a practical decision-making framework for decision makers (DMs) to use in evaluating interdisciplinary strategic approaches to degree program development. A framework based on ordinal game theory was applied using a recent decision to create an interdisciplinary business analytics program at a small, public university. The optimal Nash, in which each decision maker receives the most desirable outcome, was determined. The proposed methodological framework can be used for the design, evaluation, and postcommitment support of any interdisciplinary degree program.